CLASSIFYING CATEGORY NAMES IN VIETNAMESE WIKIPEDIA - Tạ Hoàng Thắng (Tạp chí Khoa học Đại học Đà Lạt)
Wikipedia is famous to be the biggest encyclopedia currently,the purpose of which is to spread knowledge for everyone in the world. By using robots in the process of article generation, Vietnamese Wikipedia is one of 13 language projects which has more than 1 million articles. However, this raises a lot of challenges for Vietnamese Wikipedia in article quality improvement, category classification, anti-vandalism and other tasks. In this paper, we classify categories in Vietnamese Wikipedia, particularly in category taxonomy and naming conventions. The crucial method is to adopt standards and category taxonomy in the English project, the biggest Wikipedia project in term of the amount of contributed information. Then we apply these to Vietnamese Wikipedia. To do this, we have to combine many social methods as well as techniques to gain expected results. The evaluation of category names and data results from Wikidata which we obtained is a first step to build a tool to translate English categories into Vietnamese categories.